Bolting control of a coal roadway under multi-seam mining – a case study - Zhou, Kunyou; Wu, Jiaxuan; Kann, Jiliang; Yang, Ke; Zhao, Xiangzhuo; Li, Yunpeng (Archives of mining sciences = Archiwum górnictwa, 2024)
The stress field of the roadway under multi-seam mining is complex due to multiple mining disturbances. The bolting control of the roadway under multi-seam mining has attracted wide concern. Moreover, conventional metal supporting materials in the coal rib are prone to sparks when shearer works, and new bolting materials are urgently needed. Taking a track roadway under multi-seam mining in China as the engineering case, the mining-induced stress field of the track roadway under multi-seam mining was investigated through numerical simulation and lab and field tests. The test evaluated the mechanical behaviour of FRP bolts and rebar bolts, as well as their anchorage performance under different conditions. Comparative analysis was conducted on the deformation and failure characteristics of the roadway under different bolting parameters to determine an optimised bolting scheme for the track roadway in the I011501 working face. The results show that the goafs and the remaining coal pillars in the overlying coal seams increase the stress in the track roadway in the I011501 working face, especially for the lower rib and roof. The tensile force of the 27 mm-diameter FRP bolt is 1.2 times that of the 22 mm-diameter rebar bolt. The shear strength of the full-length anchored FRP bolt is 70.8% higher than that of the end-anchored bolt. The peak stress of the full-length-anchored bolt is in the shallow coal and rock mass. The optimised bolting scheme of the track roadway subject to multi-seam mining is determined, and the cost of the optimised bolting scheme is lower by about 25.2%, as compared with the primary bolting scheme. Numerical simulation and field application results indicate that the optimised bolting scheme can significantly reduce the deformation and plastic failure of the track roadway in the I011501 working face, which is under multi-seam mining conditions.